Rastafari in Germany: Jamaican Roots and Global–Local Influences. Issue 4 (1st December 2020) - Wakengut, Anastasia
Abstract: The Rastafari movement arose in Jamaica in the 1930s and spread from that small island to a variety of areas around the world. Having emerged as a response to colonial legacies, racialization, and racial oppression, the movement of marginalized black Jamaicans transcended its local Caribbean borders and became a way of life for people of very diverse cultural origins. Rastafari, born within a tradition of resistance in Jamaica, helped its adherents reconstruct their "black consciousness" and African heritage. The worldview of the Afro‐Caribbean diaspora challenged established colonial views in the struggle for social justice. Also for many people in the West, this worldview became a source of spirituality as well as a philosophy criticizing Eurocentric assumptions of superiority. The Rastafari philosophy spread in Europe, producing a multicultural phenomenon. I focus on Rastafari in Germany, its peculiarities and similarities to, as well as its differences from, the Jamaican movement. This study poses questions about identity in the Rastafari movement in Germany and explores crucial issues in Rastafari, such as identity transformation, identity work, selfidentification, representation, cultural resistance, and globalization. My argument is that "Africanness" and "black consciousness" can be adjusted and interpreted in a European context as a cluster of ideas and symbols that offer German Rastafarians identification and embody social justice.